2003
DOI: 10.1091/mbc.e02-05-0247
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Glycogen Synthase Kinase-3 Activates Msn2p-dependent Transcription of Stress Responsive Genes

Abstract: The yeast Saccharomyces cerevisiae has four genes, MCK1, MDS1 (RIM11), MRK1, and YOL128c, that encode homologues of mammalian glycogen synthase kinase 3 (GSK-3). A gsk-3 null mutant in which these four genes are disrupted showed growth defects on galactose medium. We isolated several multicopy suppressors of this growth defect. Two of them encoded Msn2p and phosphoglucomutase (PGM). Msn2p is a transcription factor that binds to the stress-response element (STRE). PGM is an enzyme that interconverts glucose-1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 45 publications
(75 reference statements)
3
82
0
Order By: Relevance
“…3A, lanes 6-9). Most of the Mck1-dependent genes were found in other studies to be targets of the stress-activated transcription factors Msn2 and Msn4 (Gasch et al 2000;Causton et al 2001), which depend on Mck1 for maximal transcription activity in a variety of stressful environments (Hirata et al 2003). Of the 54 members of this group that depended on Mck1 in both strain backgrounds, none was affected reproducibly by the loss of either Tcn1/Crz1 or Rcn1 (lanes 2-5,10,11), suggesting that cross talk from the calcium signaling pathway was not necessary for Mck1 function.…”
Section: Mck1 Functions In the Same Pathway As Rcn1mentioning
confidence: 83%
See 1 more Smart Citation
“…3A, lanes 6-9). Most of the Mck1-dependent genes were found in other studies to be targets of the stress-activated transcription factors Msn2 and Msn4 (Gasch et al 2000;Causton et al 2001), which depend on Mck1 for maximal transcription activity in a variety of stressful environments (Hirata et al 2003). Of the 54 members of this group that depended on Mck1 in both strain backgrounds, none was affected reproducibly by the loss of either Tcn1/Crz1 or Rcn1 (lanes 2-5,10,11), suggesting that cross talk from the calcium signaling pathway was not necessary for Mck1 function.…”
Section: Mck1 Functions In the Same Pathway As Rcn1mentioning
confidence: 83%
“…6A). A large fraction of these Mck1-dependent genes was found to be targets of the Msn2 and Msn4 transcription activators (Gasch et al 2000;Causton et al 2001) that are highly dependent on Mck1 in response to a variety of cellular stresses (Hirata et al 2003). A recent study suggested high Ca 2+ conditions increase MCK1 gene expression and Mck1 function (Mizunuma et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of p38 increases insulin sensitivity in skeletal muscle in a manner that is independent of contractile induced insulin sensitivity [105], p38 activates the transcriptional coactivator PGC-1α by phosphorylation, thereby regulating the induction of mitochondrial respiration in muscle [106,107] where PGC-1α plays a role in fiber type switching [108]. The yeast homologue of GSK3β is involved in nutrient sensing and the stress response [109], In mammals, GSK3β is a negative regulator of JNK [110] and is involved in insulin sensitivity in skeletal muscle [111]. Interestingly both JNK and p38 are activated by ROS signaling from the mitochondria [112].…”
Section: Stress Oxidative Stress and Longevitymentioning
confidence: 99%
“…In order to identify that the array is indeed treated with sorbitol, a column of control cells expressing Msn2-GFP can in our setup be added to the cell array when a complete Hog1 nuclear localization is anticipated. Msn2 is a transcription factor that regulates the yeast general stress responses and is regulated by several pathways [27][28][29]. Msn2 activation is thus induced by several different stresses of which one is high osmolarity.…”
Section: The Use Of Control Cells Within the Cell Arraymentioning
confidence: 99%